2005
DOI: 10.1038/sj.ejhg.5201370
|View full text |Cite
|
Sign up to set email alerts
|

Association between SLC11A1 (formerly NRAMP1) and the risk of sarcoidosis in Poland

Abstract: Sarcoidosis (SA) is a systemic granulomatous disorder of unknown etiology characterized by T helper 1-type inflammatory responses at sites of disease with signs of B cell hyperactivity. Like rheumatoid arthritis and diabetes, an infectious etiology has frequently been postulated but no single infectious trigger definitively identified. Polymorphic alleles at SLC11A1 have previously been associated with susceptibility to both the putative infectious agents and to these autoimmune disorders. We therefore investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 33 publications
0
36
1
11
Order By: Relevance
“…A possible explanation for this is that the assay for IS6110 may not have been sufficiently sensitive to detect the very small quantity of M. tuberculosis genome in tissue from SA patients or that M. tuberculosis is present but the strains do not contain IS6110. Another possible explanation for the negative molecular results is that a small numbers of organisms provoke an intense inflammatory response, analogous to tuberculoid leprosy (3,4). It is also suggested that the agents associated with sarcoidosis are not whole mycobacteria but their antigens, e.g., mycobacterial hsp (7,8).…”
mentioning
confidence: 99%
“…A possible explanation for this is that the assay for IS6110 may not have been sufficiently sensitive to detect the very small quantity of M. tuberculosis genome in tissue from SA patients or that M. tuberculosis is present but the strains do not contain IS6110. Another possible explanation for the negative molecular results is that a small numbers of organisms provoke an intense inflammatory response, analogous to tuberculoid leprosy (3,4). It is also suggested that the agents associated with sarcoidosis are not whole mycobacteria but their antigens, e.g., mycobacterial hsp (7,8).…”
mentioning
confidence: 99%
“…However, some experiments demonstrated that the STRs located in the proximity or within a gene can regulate gene expression 40 that may cause human diseases. 41 Recently, different studies [42][43][44] have reported that common alleles of dinucleotide STRs, whose length variation are known to modulate promoter activity, conferred susceptibility to diseases. In the same way, D4S3454 within the CXCL2 promoter could be playing an important role in the regulation of transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis, the previously mentioned systemic disease associated with MAP, is also associated with polymorphisms of the SLC11A1 gene (Dubaniewicz et al, 2005). Susceptibility to mycobacterial diseases tuberculosis, leprosy and Buruli's ulcer are associated with polymorphism of the SLC11A1 gene (Stienstra et al, 2006).…”
Section: Slc11a1 In Infectious and Autoimmune Diseasementioning
confidence: 97%